Cardiovascular effects of exogenous adrenomedullin and CGRP in Ramp and Calcrl deficient mice - Pawlak, J.B. (Peptides, 2016)
Adrenomedullin (AM) and calcitonin gene-related peptide (CGRP) are potent vasodilator peptides and serve as ligands for the G-protein coupled receptor (GPCR) calcitonin receptor-like receptor (CLR/Calcrl). Three GPCR accessory proteins called receptor activity-modifying proteins (RAMPs) modify the ligand binding affinity of the receptor such that the CLR/RAMP1 heterodimer preferably binds CGRP, while CLR/RAMP2 and CLR/RAMP3 have a stronger affinity for AM. Here we determine the contribution of each of the three RAMPs to blood pressure control in response to exogenous AM and CGRP by measuring the blood pressure of mice with genetic reduction or deletion of the receptor components. Thus, the cardiovascular response of Ramp1(−/−), Ramp2(+/−), Ramp3(−/−), Ramp1(−/−)/Ramp3(−/−) double-knockout (dKO), and Calcrl(+/−) mice to AM and CGRP were compared to wildtype mice. While under anesthesia, Ramp1(−/−) male mice had significantly higher basal blood pressure than wildtype males; a difference which was not present in female mice. Additionally, anesthetized Ramp1(−/−), Ramp3(−/−), and Calcrl(+/−) male mice exhibited significantly higher basal blood pressure than females of the same genotype. The hypotensive response to intravenously injected AM was greatly attenuated in Ramp1(−/−) mice, and to a lesser extent in Ramp3(−/−) and Calcrl(+/−) mice. However, Ramp1(−/−)/Ramp3(−/−) dKO mice retained some hypotensive response to AM. These results suggest that the hypotensive effect of AM is primarily mediated through the CLR/RAMP1 heterodimer, but that AM signaling via CLR/RAMP2 and CLR/RAMP3 also contributes to some hypotensive action. On the other hand, CGRP’s hypotensive activity seems to be predominantly through the CLR/RAMP1 heterodimer. With this knowledge, therapeutic AM or CGRP peptides could be designed to cause less hypotension while maintaining canonical receptor-RAMP mediated signaling.